Sufistic Eco-Theology–Based Arabic Language Education: An Environmental Spirituality Approach to Language Learning - Akbar, M. Taufiq; Nasri, Ulyan; Hajras, Multazam (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study is motivated by the limited integration of spiritual values and ecological awareness in Arabic language education, which has predominantly emphasized linguistic competence while neglecting ethical and spiritual dimensions. In fact, the Arabic language is epistemologically connected to Islamic teachings, including Sufistic eco-theology that views nature as a manifestation of divine signs. This research aims to analyze and formulate a Sufistic eco-theological approach to Arabic language education as a means of fostering environmental spirituality within language learning. Employing a qualitative approach, this study applies library research and conceptual analysis of Sufistic literature, Islamic eco-theology, and language education theories. The research stages include examining the core concepts of Sufistic eco-theology, analyzing their relevance to Arabic language learning, and developing an integrative instructional framework. The findings reveal that integrating Sufistic eco-theological values into Arabic language education enriches instructional materials, strengthens students’ spiritual-affective dimensions, and cultivates ecological awareness grounded in Islamic values. The study concludes that a Sufistic eco-theological approach offers a viable alternative paradigm for developing holistic and transformative Arabic language education.